From Pilkades to Presidential Election? Roadmap and Obstacles of E-Voting in Indonesia's Digital Democracy - Farhanuddin; Muhammad; Gustiana; Nas, Jayadi (Master Program of Sociology, Universitas Malikussaleh,, 2025)
The development of information technology has encouraged various countries to adopt digital electoral systems, including Indonesia, which has started implementing e-voting at the village head election (Pilkades) level. However, the transition to digital elections still faces various structural and institutional challenges. This research aims to explore the roadmap and obstacles in the implementation of e-voting as part of the digital democracy architecture in Indonesia. The research method used is descriptive qualitative with data collection techniques in the form of in-depth interviews with three resource persons: The Chairman of the 2019 KPU, an election law academic, and a former regional head who had implemented e-voting in his region. The data analysis technique used is thematic analysis, to identify the main patterns in the interviewees' narrative. The results show that e-voting has significant benefits to the efficiency and transparency of the electoral process at the local level, and is well received by the public. However, its expansion to the national level faces major challenges such as infrastructure readiness, digital divide, political elite resistance, and the absence of comprehensive regulations and oversight mechanisms. This research highlights the importance of a phased and hybrid approach, as well as the need to strengthen institutional credibility to build public trust in electoral technology. The significance of this research lies in its contribution to designing a contextualised model of electoral digital transition in developing countries. The practical benefits are as policy input for governments and electoral administrators in building a digital democracy roadmap that is inclusive, equitable and adaptive to local challenges.